Coexisting predictors for undernutrition indices among under-five children in West Africa: application of a multilevel multivariate ordinal logistic regression model - Abebew Aklog Asmare; Awoke Seyoum Tegegne; Denekew Bitew Belay; Yitateku Adugna Agmas (BMC Nutrition)
Abstract Background Due to its immediate and long-term implications for population health and socioeconomic advancement, children’s nutritional status is especially crucial. It is the main reason for morbidity and mortality in children under five. Therefore, this study aimed to investigate predictors for under-nutrition indices among under-five children in West Africa. Method The study was conducted in 14 countries in West Africa. A weighted total sample of 35,162 under-five children was included. Considering the impact of other predictors such as maternal, child, and socioeconomic variables, a multilevel multivariate partial proportional ordinal logistic regression model was conducted to analyze the relationship between stunting, wasting and underweight. Result Among the participants in the study, approximately 27.7% were stunted, with 17.9% moderately stunted and 10.8% severely stunted. Additionally, about 18.6% (13.3% moderately and 5.3% severely) were underweight, and 9% (6.7% moderately and 2.3% severely) were wasted. More than half of the children (51.1%) were male, and 36.6% lived in urban areas. Compared to singleton children, a child with multiple birth types was 2.701, 3.740, and 1.777 times more likely to be stunted, underweight, and wasted, respectively. Conclusion The findings in the current study revealed a direct correlation among underweight status, wasting, and stunting. Furthermore, even when ignoring the effects of other independent variables, underweight was found to serve as a composite measure of stunting and wasting when examining the link between these three indicators. The results identified several common predictors significantly associated with all three undernourishment indices. Therefore, governments and non-governmental organizations should prioritize public health interventions aimed at improving parental education and increasing antenatal care visits to enhance the nutritional status of under-five children. More attention should be given to improving healthcare delivery at health facilities and homes, promoting children’s health education, and ensuring access to clean drinking water sources.